Teenage Pregnancy and Obstetric Outcome: A Comparative Study In Urban Nigeria - Eugene, Ikeanyi; Israel, Jeremiah; Atombosoba, Ekine (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: Teenage pregnancy is a worldwide problem that poses social and health concerns in both industrialized and developing countries. This study therefore sought to evaluate the relevance of age at first pregnancy on obstetric performance. Methods: This was a case control analytical, observational study of teenage women as study group and older control subgroup aged 20-34 years that had their first childbirth between 2009 and 2013 at a mission Hospital in Benin City, South- South, Nigeria. Statistical analysis was with computer statistical software with statistical significance set at p<.05. Results: The incidence of teenage nullipara in this study was 1.1%. The study group were more likely to be unmarried (OR=9.6, P<0.001), unemployed (OR=6.6, P=0.001), attained below secondary level of education (OR=8.4, P< 0.001) and less likely to attain post secondary level of education (OR=0.05, P<0.001), lack prenatal care (OR=2.1, P=0.15),have vaginal delivery (OR: 5.7, P=0.01), less caesarean section rate (OR=0.2, P=0.01), weighed less at booking and last prenatal visits (P<0.001) respectively and neonates weighing less at birth (t=2.1, P=0.04). Conclusion:Teenage pregnancy was more a social than an obstetric problem. Adequate empowerment before reproductive role, discouragement of early marriage and or childbearing is hereby proffered.